STRATEGI KOMUNIKASI MALU DONG COMMUNITY DALAM MENGEDUKASI MASYARAKAT UNTUK PEDULI TERHADAP KEBERSIHAN LINGKUNGAN - Sanjiwani, I.A Agung Anindia; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABS TRACT     T he growth of population a nd the l ack of awareness of the public to k eep the environment h ave a direct i mpact on i ncreasing the v olume of g arbage and s ewage i n the c i t y of Denpasar. P r oduction of g arbage i n t he c i ty of D enpasar has i n cr eased each y e ar, from 2 016 t he v olume of a g arbage r e ached 850 tons i n day and 900 tons i n 2017. Malu Dong Community moved to eradicate s uch phenomena and do a c ommunication s trategy. T his r esearch aims to provide a n overview and explanation of the r e l ated c ommunication s trategy undertaken b y the MDC i n educating   the  p ublic   to   c are  about   the   c l e anliness   of  t he   environment.  T he   object  o f  this r esearch i s M a l u D ong C ommunity. type o f this r esearch i s a d escriptive q ualitative d ata c ollection techniques f orm of i nterviews, observation, and document S t udies. T h e r esults of t his r esearch are as follows, MDC are educating their audience by c ollecting l i tters i n the middle of cr owds and targeting each of their audience w i th d i fferent approach, and a l s o t hey are u tilizing outdoor   media,  f or   example,  f l ags   i n  order   to  properly   deliver   a  message  to  their   target audiences.     Keywords:  C ampaign,  Communication  S trategy,  G arbage,  M a l u  Dong  Community